IMPLEMENTASI KEBIJAKAN LAYANAN DIGITAL PROGRAM SAMSAT KELILING DI KABUPATEN MAJALENGKA - Amiruddin Setiawan (Jurnal Ilmu Administrasi CENDEKIA, 2021)
ABSTRACTThe research on the mobile samsat program is regulated in the policy of the Presidential Regulation of the Republic of Indonesia Number 5 of 2015 concerning the Implementation of the One-Stop Administration of Motorized Vehicles in Article 22 to form auxiliary units, one of which is the mobile samsat program as an effort to increase motor vehicle tax revenues. It was found that the mobile samsat program had not run optimally. The purpose of this study was to determine the implementation of the mobile Samsat program in Majalengka Regency which was organized by the Majalengka Samsat office.This type of research, the researcher uses qualitative research methods that are described descriptively. Data collection techniques were carried out using interview techniques, participant observation, literature study and documentation. The informants in this study were 15 people consisting of the head of the income and determination section, mobile Samsat officers, employees in the field of data management and tax potential, as well as taxpayers who had made payments in the mobile Samsat program by using the theory of policy implementation of Donald Van Metter and Carl Van Horn. .The results showed that the implementation of program policies was quite good but not yet fully optimal. This is based on the dimensions of size and policy objectives, there is a decrease in income, from resources there is still a shortage of human resources, mobile samsat cars, the network system is affected by the weather, the location of the implementation of the mobile samsat program is less strategic and the lack of waiting seats, from the characteristics of the implementing agency it is quite good and structured, from attitudes and tendencies that are quite good but lack of understanding of the legal basis of the mobile Samsat program, from communication between organizations, the lack of socialization of the program to the community and the lack of information about administrative requirements. From the economic, social and political environment it runs smoothly. Recommendations are to add the human resources involved, add a mobile Samsat car unit, optimize the socialization of the program either directly or through the mass media. Keyword : Samsat Around, Presidential Decree, Policy Implementation